Etude de populations de Glycymeris (Bivalvia, Glycymerididae) du Miocène d'Aquitaine, Sud-Ouest de la France - Cahuzac, B. (2010)
Abundant crops of Glycymeris have been made in the neritic bioclastic deposits of the Aquitaine Basin. After an outline about the Chattian taxa, the 5 Lower Miocene lineages are presented; G. cor is plainly predominant. Then, the Middle Miocene faunas are also detaiIed, G. inflatus and G. bimaculatus being the most frequent taxa. A test of biometrical analysis about the G. cor species is presented.